(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Women with Systemic Lupus Erythematosus (SLE) continue to face substantial risks during pregnancy due to the complex interactions between Lupus and pregnancy. Since SLE predominantly affects women of childbearing age, it is frequently encountered during pregnancy and is associated with increased maternal and fetal risks compared to pregnancies in healthy women. Adverse pregnancy outcomes in women with SLE include spontaneous miscarriage, fetal growth restriction, preeclampsia, sudden intrauterine death, and preterm delivery. Methodology: Discussion cross sectional study included 30 patients diagnosed with SLE in pregnancy from the Fetomaternal Medicine Department between January 2023 and August 2024. The study aimed to evaluate maternal and fetal outcomes in pregnancies complicated by SLE. Result: This study examined 30 cases of pregnancy in women diagnosed with SLE, each pregnancy being considered as a individual case. Most patients were between the ages of 18 35, with 80% being nulliparous and a mean SLE disease duration of 3.93±2.23 years. Most patients were in clinical remission prior to pregnancy. Pregnancy complications included SLE flares in 3 (10%) cases, missed abortion in 3 (10%), premature rupture of membranes (PROM) in 1 (3.33%), preterm labor in 8 (26.67%), preeclampsia in 2 (6.67%), and intrauterine death in 3 (10%) cases. Additionally, 22 (73.33%) patients were admitted after reaching 37 weeks of gestation. Delivery was most frequently caused by cesarean section (70%), with 4 (13.33%) of the infants being low birthweight. Conclusion: A multidisciplinary approach, including close medical, obstetric, and neonatal monitoring, is essential to optimize maternal and fetal outcomes in pregnancies affected by SLE Bangladesh J Obstet Gynaecol, 2025; Vol. 40(1): 24-29